Laboratory Benchmark of n ≥ 4 Dielectronic Recombination Satellites of Fe xvii - Grell, Gabriel J. (2024)
Funding Information: Research was funded by the Max Planck Society (MPS), Germany. We acknowledge support from NASA’s Astrophysics Program. G.G. acknowledges support under NASA award No. 80GSFC21M0002. M.L. acknowledges support from NASA's Astrophysics Division. P.A. acknowledges the support from Fundação para a Ciência e a Tecnologia (FCT), Portugal, under grant No. UID/FIS/04559/2020 (LIBPhys) and High Performance Computing Chair—a R&D infrastructure based at the University of Évora (PI: M. Avillez).C.S. acknowledges support from NASA under award number 80GSFC21M0002 and by Max Planck Society (MPS), Germany. Publisher Copyright: © 2024. The Author(s). Published by the American Astronomical Society.